IMPLEMENTASI MODEL CUSTOMER RELATIONSHIP MANAGEMENT UNTUK FUNGSI LAYANAN UMUM PADA ERA TATANAN BARU - Mahardhika Berliandaldo; Achmad Chodiq; Sutarno Sutarno; Heru Eko Prasetyo (Universitas Halu Oleo, 2021)
Customer Relationship Management or CRM is a new approach to managing relationships between organizations and customers. In the era of the new order, especially during the current Covid-19 pandemic, digitizing public service functions carried out by the General Bureau of LIPI will play an important role in supporting the smooth running of the organization's operations. Customer satisfaction is highly dependent on the service process provided by executing service functions. In order for public service functions to run properly, it is necessary to carry out analysis in exploiting customer data in order to create increased value for the organization and customers by using Value Chain model analysis. Furthermore, to describe the implementation of CRM in public service functions, the implementation of the model applied is to use Payne's five-process model. This model describes the five core processes in CRM, namely the strategy development process, the value creation process, the multichannel integration process, the performance appraisal process and the information management process. The strategy for implementing this model is used so that the results obtained can run as expected. That way, customer satisfaction will be a top priority in implementing CRM in the general service function at LIPI.